How Positive Social Perceptions and Attitudes Toward Entrepreneurship Foster Inclusive Entrepreneurial Outcomes: A Cross-Country Comparative Study - Aaron A. Vargas-Zeledon; Su-Yol Lee (SAGE Open)
Inclusive entrepreneurship has increasingly received attention as a promising means of simultaneously fostering economic growth and mitigating inequality. This study explores the motivational enablers that facilitate inclusive entrepreneurship and how they do so, using a given country’s economic and entrepreneurial contexts as moderators. Results of the hierarchical regression analysis using 987 country-year cases compiled from the Global Entrepreneurship Monitor (GEM) indicate that entrepreneurial ability positively affects general and inclusive entrepreneurship outcomes. In contrast, entrepreneurial optimism contributes to facilitating general entrepreneurial activity. This study does not find evidence of social recognition and career desirability effects on entrepreneurship outcomes. The country’s economic and entrepreneurship contexts partially moderate the relationship between the motivational enablers and entrepreneurship outcomes. The country’s economic context intensifies the positive effect of entrepreneurial ability on TEA, and the country’s entrepreneurship environment accentuates the positive effect of career desirability on TEA and the positive effect of social recognition on inclusive entrepreneurial outcomes. Notably, positive social perceptions of and attitudes toward entrepreneurship are more evident in emerging economies than in developed countries. As one of the first to explore inclusive entrepreneurship from a motivational lens, this study provides significant implications for academics and policymakers who wish to foster inclusive entrepreneurship.